Implementation of Implementation of Providing Legal Assistance for Disappointed Communities in the View of Islamic Law - Lailiyah Lailiyah; Akhmad Shadikin; Didi Sukardi (Journal of Law and Social Politics, 2023)
The implementation of the provision of legal aid to the underprivileged at the Legal Aid Institute (LBH) plays a very important role in providing legal assistance to underprivileged people who are seeking justice. To obtain legal assistance, submit a written application containing the identity of the applicant (KK or KTP), attach an SKTM (certificate of incapacity) and briefly describe the case, submit case documents, and survey the location of the house. The duties and powers of the Legal Aid Institute (LBH) provide legal assistance through litigation and non-litigation to people who can't afford it. The inhibiting factors in providing legal aid are that not all people know about legal aid institutions and lack of legal education. The view of Islamic law on the provision of legal aid to the poor in the Legal Aid Institute (LBH) has become an order from Allah SWT in upholding Islamic law with the principles of justice, equality, and mutual assistance, that is, everyone has the right to their rights and everyone has the same position before the law. Implementation of the provision of legal aid to people who cannot afford it is the application of the principle of mutual help in terms of kindness and piety. This act is a worship relationship between fellow beings to benefit the people.